Angiopoietin‐Like Protein 4 Is a High‐Density Lipoprotein (HDL) Component for HDL Metabolism and Function in Nondiabetic Participants and Type‐2 Diabetic Patients - Long‐Yan Yang; Cai‐Guo Yu; Xu‐Hong Wang; Sha‐Sha Yuan; Li‐Jie Zhang; Jia‐Nan Lang; Dong Zhao; Ying‐Mei Feng (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2017)
BackgroundANGPTL4 (angiopoietin‐like protein 4) is a LPL (lipoprotein lipase) inhibitor and is present in high‐density lipoprotein (HDL). However, it is not defined whether ANGPTL4 in HDLs could affect HDL metabolism and function in type 2 diabetes mellitus (T2DM). Methods and ResultsANGPTL4 levels in the circulation and HDLs were quantified in nondiabetic participants (n=201, 68.7% females) and T2DM patients (n=185, 66.5% females). HDLs were isolated from nondiabetic controls and T2DM patients to assess cholesterol efflux or subjected to endothelial lipase (EL)‐overexpressed HEK293 cells for EL hydrolysis in vitro. The association between ANGPTL4 in HDLs and HDL components and function was analyzed in nondiabetic participants or diabetic patients, respectively. Plasma or HDLs of ANGPTL4+/+ and ANGPTL4−/− mice was subjected for cholesterol efflux or EL hydrolysis, respectively. ANGPTL4 levels in the plasma and HDLs were 1.7‐ and 2.0‐fold higher in T2DM patients than nondiabetic controls, respectively (P<0.0001). Multivariable analysis demonstrated that per 1 doubling increase of ANGPTL4 levels in HDLs, the changes amounted to +0.27% cholesterol efflux (P=0.03), +0.06 μg/mL apolipoprotein A‐I (P=0.09) and −9.41 μg/L serum amyloid A (P=0.02) in nondiabetic controls. In T2DM patients, the corresponding estimates were −0.06% cholesterol efflux (P=0.10), −0.06 μg/mL apolipoprotein A‐I (P=0.38), and +3.64 μg/L serum amyloid A (P=0.72). HDLs isolated from ANGPTL4−/− mice showed accelerated hydrolysis by EL and reduced cholesterol efflux compared with ANGPTL4+/+ littermates. ConclusionsPhysically, ANGPTL4 in HDLs protected HDLs from hydrolysis. Resulting from increased circulating ANGPTL4 levels in T2DM, ANGPTL4 levels in HDLs were elevated but with compromised inhibitory effect on EL, leading to increased HDL hydrolysis and dysfunction.